Influence of Pelleting on Lucerne (Medicago sativa L.) Seed - Baladhiya, C S; DOSHI, J S; JOSHI, D C (Journal of Agricultural Engineering, 2012)
Lucerne seeds were pelletized using a developed seed pelletizer. The seed pelletization process was standardized using locally procured gum arabic solution (20%) in water as binding material for coating materials like pond clay, sand, neem leaf powder, biogas plant spent slurry powder. Pelletization efficiency was greater than 90% in most of the cases in a range of 84-92%. Sphericity ranged from 0.80 to 0.89. The pellet sphericity, bulk density and 1000 pellet mass increased with duration of pelletization. The unpelleted seeds did not fulfill the required criteria of the Indian Minimum Seed Certification Standard of minimum germination per cent of 80. The fresh and dry mass of germinated seedlings was more in the pelleted seed compared to unpelleted seed. The use of 100% pond clay, with pelleting for 30 min, resulted in pellets giving higher germination (89%) and vigour index.